"AN EMPIRICAL ANALYSIS OF EFFICIENCY AND STOCK RETURNS: EVIDENCE FROM INDIAN BANKS" - Sait, Shaista (2013)
India is a booming market that is likely to be one of the top 10 world banking regions it is therefore important for us to learn and take note of this very important sector for the health of the Indian economy. Most of the previous studies have analyzed limited datasets in years prior to the GFC primarily adopting DEA which has several limitations discussed later. The purpose of this research is to examine the banking efficiency in India from 2006 to 2011 using SFA. This paper is the first to my knowledge to not only link the profit and cost efficiency scores of the publicly listed Indian banks and their stock price returns using a two stage stochastic frontier modelling estimation strategy but also employs a more recent database that takes into consideration vitally the years of the GFC. The empirical findings of this research suggest that Indian banks profit efficiency scores deteriorated substantially during the global meltdown in 2008 since they were using a low proportion of loan loss provisions and injecting high levels of equity capital as a cash buffer instead of a risk control variable to withstand the crisis. The cost efficiency scores in contrast were soaring high during this adversity largely because majority of the Indian banks were following the strategy of cost containment rather than profit maximization. The profit and cost efficiency estimates of the Indian banks tend to crossover seldom witnessed in banking literature which usually occurs mainly in highly competitive markets hence due to these pressures there are diseconomies of scale in the Indian markets which causes the profit and cost efficiency estimates to move in the opposite direction contrary to what is expected. While analyzing the link between efficiency and stock performance the changes in profit efficiency of Indian banks are statistically significant and positively related to stock returns however in contrast to previous researches an interesting finding is that the changes in cost efficiency are statistically significant and negatively associated with the stock returns.